2020
DOI: 10.1021/acsami.0c10579
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Single Oriented Oxide Superlattices on Silicon Using Various Template Techniques

Abstract: To benefit from the diverse functionalities of perovskite oxides in silicon-based complementary metal oxide semiconductor (CMOS) technology, integrating oxides into a silicon platform has become one of the major tasks for oxide research. Using the deposition of LaMnO 3 /SrTiO 3 (STO) superlattices (SLs) as a case study, we demonstrate that (001) single oriented oxide SLs can be integrated on Si using various template techniques, including a single-layer buffer of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…[163c,179] This has served as a basis by Chen et al to deploy various techniques including MBE, pulsed laser deposition (PLD), and the introduction of multiple-layer buffer to integrate LaMnO 3 /STO(001) into Si-based systems. [180] By at-tempting different integration techniques, the system comprising STO/Ca 2 Nb 3 O 10 is shown to possess the highest sample crystallinity due to the small lattice mismatch between the layers while the MBE-grown Si-integrated system produces a system with significantly suppressed saturation magnetization due to the presence of a large thermal strain. Even though it is still at the state of infancy, the successful integrated perovskite oxide/Si superlattice structures are ideal platforms particularly with their compatibility with existing Si-based wafer processing technology for the fabrication of highly-compact neuromorphic components and other electronic devices.…”
Section: The Way Forward-integration With Existing Technologiesmentioning
confidence: 99%
“…[163c,179] This has served as a basis by Chen et al to deploy various techniques including MBE, pulsed laser deposition (PLD), and the introduction of multiple-layer buffer to integrate LaMnO 3 /STO(001) into Si-based systems. [180] By at-tempting different integration techniques, the system comprising STO/Ca 2 Nb 3 O 10 is shown to possess the highest sample crystallinity due to the small lattice mismatch between the layers while the MBE-grown Si-integrated system produces a system with significantly suppressed saturation magnetization due to the presence of a large thermal strain. Even though it is still at the state of infancy, the successful integrated perovskite oxide/Si superlattice structures are ideal platforms particularly with their compatibility with existing Si-based wafer processing technology for the fabrication of highly-compact neuromorphic components and other electronic devices.…”
Section: The Way Forward-integration With Existing Technologiesmentioning
confidence: 99%
“…However, the obtained STO layer was actually polycrystalline in spite of the crystallinity improvement compared to the film obtained without the graphene interlayer . For the purpose of integrating functional oxides with a silicon platform, we have recently compared different templates for the growth of STO pseudo-substrate on Si, a reduced graphene oxide (rGO) among others . The present study provides more details on the STO growth mechanism and the role of rGO in this process.…”
Section: Introductionmentioning
confidence: 99%
“…29 For the purpose of integrating functional oxides with a silicon platform, we have recently compared different templates for the growth of STO pseudo-substrate on Si, a reduced graphene oxide (rGO) among others. 30 The present study provides more details on the STO growth mechanism and the role of rGO in this process. Furthermore, the potential of the as-prepared STO layer to be used as a pseudo-substrate was evaluated by overgrowing a PbZr 1−x Ti x O 3 (PZT) layer.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we used pulsed laser deposition (PLD) to prepare an STO epitaxial layer on a Si photocathode, where in between the film and the substrate a buffer layer of reduced graphene oxide (rGO) was introduced. In our previous work we demonstrated the necessity of rGO as an epitaxy template guiding the growth of STO along the preferential orientation. , To obtain the best quality of STO layer, an rGO-coated Si substrate with full coverage was adopted as the overgrown template . Moreover, it has been reported that the high electrical conductivity of rGO can accelerate the charge transfer between the semiconductor and the electrolyte and significantly enhance the PEC efficiency. , Herein, the crystal and microstructural properties of the grown STO layer were investigated and discussed using X-ray diffractometry (XRD), in situ reflection high-energy electron diffraction (RHEED), and atomic force microscopy (AFM), in comparison to the polycrystalline film where STO was directly deposited on Si without rGO.…”
Section: Introductionmentioning
confidence: 99%